Free carotenoids and carotenoids esters composition in Spanish orange and mandarin juices from diverse varieties. (1st December 2019) - Giuffrida, Daniele; Cacciola, Francesco; Mapelli-Brahm, Paula; Stinco, Carla M.; Dugo, Paola; Oteri, Marianna; Mondello, Luigi; Meléndez-Martínez, Antonio J.
Highlights: Esterification patterns different among orange and mandarin juices were identified. Monoesters were the major class of carotenoids in the samples analyzed. Unsaturated fatty acids were not detected in the esters from the samples analyzed. Differences with respect to other patterns reported by other authors were highlighted. Abstract: The carotenoid profiles of citrus fruit have been well studied, but knowledge about the xanthophylls esters pattern is more limited. In this study, the native carotenoid profiles of mandarin and orange juices were studied. Xanthophylls in oranges were esterified with lauric, myristic, palmitic and stearic acids. The fatty acids esterifying β-cryptoxanthin in mandarins were lauric, myristic, palmitic and capric acid. In oranges, the average relationships of total free carotenoids to the sum of mono-esters and di-esters were 0.82 and 1.67, respectively, and the average relationships total mono-esters to total of di-esters was 2.51. In general, the mono-ester fraction was the most significant quantitatively. In mandarins, the average relationship of total free carotenoids to the sum of mono-esters was 0.17, which is in line with the fact that β-cryptoxanthin was mostly esterified and not free (unesterified).